2018
DOI: 10.1002/mbo3.641
|View full text |Cite
|
Sign up to set email alerts
|

Serial passage through resistant and susceptible cucumber cultivars affects the virulence of Fusarium oxysporum f. sp. cucumerinum

Abstract: Fusarium oxysporum f. sp. cucumerinum (Foc) is the causal pathogen of cucumber Fusarium wilt resulting in losses to cucumber production. To investigate the effects of the selective pressures of host plants on the virulence of Foc, a low virulence isolate, foc-3b, was successively inoculated on resistant and susceptible cucumber cultivars for five generations. The virulence of the original isolate diverged; virulence was significantly strengthened after serial passage on the resistant cultivar and weakened on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…However, that the re-isolates could have arisen from an introduced contaminant cannot be entirely ruled out. To confirm provenance of re-isolates, selected marker genes (Huang et al 2019) or whole genome sequences (WGS) of the isolates and re-isolates could be compared (Malapi-Wight et al 2016;Chalupowicz et al 2019). Field inoculum was significantly more virulent than all other isolates in every aspect: lesions appeared earlier, were longer, and the AUDPC of both disease incidence and lesion length were greater, confirming that all isolates used in this study, and their re-isolates, were low-virulent isolates.…”
Section: Isolatesupporting
confidence: 52%
See 2 more Smart Citations
“…However, that the re-isolates could have arisen from an introduced contaminant cannot be entirely ruled out. To confirm provenance of re-isolates, selected marker genes (Huang et al 2019) or whole genome sequences (WGS) of the isolates and re-isolates could be compared (Malapi-Wight et al 2016;Chalupowicz et al 2019). Field inoculum was significantly more virulent than all other isolates in every aspect: lesions appeared earlier, were longer, and the AUDPC of both disease incidence and lesion length were greater, confirming that all isolates used in this study, and their re-isolates, were low-virulent isolates.…”
Section: Isolatesupporting
confidence: 52%
“…The mechanisms underlying these changes in virulence were not investigated explicitly during these studies. However, sequence variations (although without a correlation with virulence alterations; Wang et al 2008), and moderated virulence gene expression (Huang et al 2019) were both observed. Thus, in these pathosystems, alterations in virulence with passaging through the host may have been be due to sequence mutations.…”
Section: Isolatementioning
confidence: 93%
See 1 more Smart Citation
“…In a previous study, a mild virulence isolate, foc-3b, was successively inoculated on resistant and susceptible cucumber cultivars for five generations. The virulence of the original isolate diverged rapidly; virulence was significantly increased after serial passage on the resistant cultivar, especially in the fourth generation, but decreased on the susceptible plants ( p < 0.05) [8]. This suggests a specific interaction with the plant that selects for enhanced virulence in the pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a few pathogenicity-related genes of Foc have been identified, mainly including fga1 , fga2 and fgb1 that encodes G-protein α and β subunits [1113] and FocVel1 that encodes a velvet protein [14]. In addition, several virulence factors of F. oxysporum involved in synthesis or regulation of plant cell wall degradation enzymes (CWDEs) and in breaking plant defense have been found to relate to pathogenicity differentiation of Foc [8]. Pathogenicity related genes are often encoded in accessory genome regions of F. oxysporum and up-regulated during infection [1518].…”
Section: Introductionmentioning
confidence: 99%